Participation of Indian Rural Women In Rural Development: Empowering Indian Rural Women in Rural Development (Journal of Advances and Scholarly Researches in Allied Education, 2012)
This paper highlights the Participation of Indian ruralwomen in rural development like agriculture and its allied fields. It is arguedthat the rural women in India have been actively involved in agriculture andits allied fields. Rural women’s work ranges from crop production to harvestingoperations, from live stockrearing to raising babies. In addition to her daily work routine, consistingof, cooking, cleaning, and other domestic chores, rural women are also heavilyinvolved in all aspects ofcountry’s agricultural sector. From crop production to livestock rearing, ruralwomen are expected to regularly engage both domestic and commercial aspects ofsociety. Despite such a hugecontribution, her role has yet not been recognized.  The paper recommends afair treatment to the rural women and calls for social upliftment by enhancing education, employment, training, andhealth care facilities.